Diagnosis of Inherited Platelet Function Disorders using two different Diagnostic Approaches - Ahmed, Muhammad waleed; Khattak, Saeed Akhtar Khan; Zahir, Saima; Zahoor, Sumaira; Umar, Muhammad; Tahir, Nazish (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of immunophenotyping by flow cytometry (FC) and light transmission aggregometry (LTA) in diagnosing inherited platelet function disorders (IPFDs) i.e., Glanzmann thrombasthenia (GLT) and Bernard-Soulier syndrome (BSS).Study Design: Prospective longitudinal study.Place and Duration of Study: Armed Forces Institute of Pathology Rawalpindi, Pakistan from Jul 2020 to Jun 2022.Methodology: A total of 76 patients were included in the study based on their clinical presentation and elevated bleeding time, as assessed using the ISTH-SSC Bleeding Assessment Tool severity score. Flow cytometry was performed on blood samples collected in EDTA anticoagulant to detect platelet membrane glycoproteins (CD41, CD61, CD42a, and CD42b). In contrast, LTA was used to record platelet responses to collagen, epinephrine, ADP, and Ristocetin, with platelet-rich plasma prepared from blood specimens collected in citrate anticoagulant.Results: A total of 76 patients were included in the study based on their clinical presentation and increased bleeding time. Amongst them 42(58.0%) were males, while the mean age was 10.61±8.74 years. Chronic history of epistaxis was the presenting symptom in majority of the patients; 26(32%). Flow cytometry revealed a total of 16 patients suffering from IPFDs (GLT=10; BSS=06) whereas LTA confirmed the diagnosis of platelet dysfunction among 14 cases (GLT=10; BSS=04). Both showed concurrent positive results in 76.5% subjects (κ=0.84) while flow cytometry showed a relatively higher value of sensitivity, specifically in patients with low plateletConclusion: Both LTA and flow cytometry show a significant level of mutual diagnostic agreement.